STRATEGIES FOR ENHANCING KINDERGARTEN STUDENTS’ ENGLISH SKILS THROUGH LEARNING IN REAL-LIFE CONTEXTS - Ririn Ambarini (ETERNAL (English Teaching Journal), 2012)
Early learning experiences are crucial to establish the foundation for the acquisition of knowledge and skills that will affect later learning and behaviour. As teaching English at the early age is very crucial, learning experiences should be thoughtfully planned and guided by the teacher. It is found out that there are still many kindergarten students who still find difficulties in learning English vocabularies for  the strategies and teaching learning media that are conveyed by the the teachers are not sufficient to support the English class in kindergarten and the English teaching learning process is still teacher-centered with less interaction between teachers and students and also between students and students. The effects of those conditions make the students pay less attention on the English activities given by their teachers, respond passively to the questions and the instructions from the teachers, and give unhappy expression when joining the English activities. Having a look at those problems, the strategies in the process of teaching learning, will contribute to the output of students’ learning. In this article, it will discuss six strategies to improve kindergarten students’ English skills through learning in real-life contexts. Those strategies are knowing the early stages of learning, developing the activities of learning in real-life contexts, developing the activities of integrated learning, developing an effective literacy environment, developing the activities of learning early numeracy in real-life contexts, and creating a supportive learning Environment.